Developing Sukuk for Research and Innovation Project - Asokawati, Adita Dyah; Sadariyah, Ayu Solihah; Nurfalah, Irfan (SMART Insight, 2023)
The growth of creative economics in Indonesia, especially in research and innovation development, has a potential appointment for improving the growth of Indonesia's economy. Most developing countries including Indonesia have a fundamental problem, namely the lack of availability of state funds and investment for infrastructure development. One form of implementation of limiting the lack of development funds of a country is to use the concept of PPP (Public-Private Partnership). Basically, the concept of PPP is not much different from the concept of sukuk in the Islamic capital market. This research tries to know how the concept of mudaraba sukuk and istisna sukuk can urge the growth of research and development sector. As we know sukuk development has grown rapidly in the world, that becomes sukuk as capital base for financing the project. Therefore, for improving this research and development sector, the writer innovates and creates skim of capital for improving research and development sector in Indonesia.